229k views
0 votes
Simplify the following expression. (3 + 8 x ) + 7 x 3 + 15x 18 x 18 + x11 x + 7

Simplify the following expression. (3 + 8 x ) + 7 x 3 + 15x 18 x 18 + x11 x + 7-example-1

1 Answer

5 votes

Given the expression;

(3+8x)+7x

First thing we need to do is open up the parenthesis as shown;


\begin{gathered} =(3+8x)+7x \\ =\text{ 3+8x+7x} \end{gathered}

Simplify by adding up the like terms as shown;


\begin{gathered} =\text{ 3 + 8x + 7x} \\ =\text{ 3 + 15x} \end{gathered}

Hence option A is correct

User Gabriele Buondonno
by
5.5k points